Hallazgo de plantas mexicanas del género Cotinus (Anacardiaceae) con características de reliquias del Terciario - Rzedowski, Jerzy; Calderon de Rzedowski, Graciela (Instituto de Ecología, A.C., 1999)
Cotinus carranzae sp. n. is described on the basis of materials collected on steep slopes of the Moctezuma river gorge in the state of Querétaro. The closely related Rhus chiangii Young, known from northeastern Durango, is also transfered to Cotinus. Both species differ from the remaining members of Cotinus in their less asymmetrical fruit, in the lack of elongate and plumose pedicels developing in the inflorescence, as well as in smaller leaves and fruits. It is concluded that C. carranzae and C. chiangii are possibly primitive members of the genus. In consequence, and considering their scarcity and ecological confinement, as well as the information obtained from the fossil record of Cotinus and from the distribution of its modern species, they are thought to represent relicts of Cenozoic paleofloras.